Astrocyte Changes in the Prefrontal Cortex From Aged Non-suicidal Depressed Patients - Qi, Xin-Rui; Kamphuis, Willem; Shan, Ling (Frontiers in Cellular Neuroscience, 2019)
Glia alterations in the anterior cingulate cortex (ACC) and dorsolateral prefrontal cortex (DLPFC) have been postulated to play an important role in the pathophysiology of psychiatric disorders. Astroglia are the most abundant type of glial cells in the central nervous system. The expression level of astrocyte markers (glial fibrillary acidic protein (GFAP), synemin-α, synemin-β, vimentin, nestin) in isolated grey matter from postmortem ACC and DLPFC were determined to investigate the possible involvement of astrocytes in depression. Donors were aged non-suicidal subjects with bipolar disorder (BPD) or major depressive disorder (MDD), and matched controls. GFAP mRNA levels were significantly increased in the ACC of BPD patients. However, GFAP immunohistochemistry showed that the area fraction of GFAP immuno-reactive astrocytes was decreased in the ACC of BPD patients, while there was no change in the cell density and integrated optical density, indicating that there might be a retraction reduction of GFAP-positive astrocyte processes and remodeling of the astrocyte network in BPD. Furthermore, in controls, DLPFC GFAP mRNA levels were significantly lower with a time of death at daytime (08:01-20:00h) compared to nighttime (20:01-08:00h). In depression, such a diurnal pattern was not present. These findings in BPD and MDD subjects warrant further studies given the crucial role of astrocytes in the central nervous system.